The influence of shadow banking, bank size, credit risk, and macroeconomics factors on return: the case of banks in Malaysia - Chan, Chi Jing; H’ng, Shiang Yih; Lem, Rui Sean; Lim, Kai Kiang; Ng, Jia Ying (2019)
The aim of this research was to examine the factors on bank profitability in all Malaysian commercial banks over the study periods between 2003 and 2017. The selected bank-specific determinants are shadow banking, credit risk and bank size. Whereas macroeconomic determinants are inflation and gross domestic product. Fixed Effect Model (FEM) and Ordinary Least Square (OLS) were used in this research to determine the significance relationship among the bank profitability and independent variables. The empirical results concluded that credit risk, gross domestic product and shadow banking had statistically significant positive influence on bank profitability whereas bank size had found out a significant negative impact on bank profitability. However, inflation has no relationship with the bank profitability.